2009
DOI: 10.3389/neuro.08.012.2009
|View full text |Cite
|
Sign up to set email alerts
|

Litter environment affects behavior and brain metabolic activity of adult knockout mice

Abstract: In mammals, the formative environment for social and anxiety-related behaviors is the family unit; in the case of rodents, this is the litter and the mother-young bond. A deciding factor in this environment is the sex ratio of the litter and, in the case of mice lacking functional copies of gene(s), the ratio of the various genotypes in the litter. Both Sex and Genotype ratios of the litter affect the nature and quality of the individual's behavior later in adulthood, as well as metabolic activity in brain nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…In other species, the sex effect is not always obvious. For example, sex did not affect aggression in pigs (D'Eath and Lawrence, 2004), while sex ratio on the other hand (Crews et al, 2009;Mendl and Paul, 1990;Namikas and Wehmer, 1978) clearly affects aggression at least in rodents. However, aggression in the later studies was tested using conspecifics in a standard resident intruder test and in this study, aggression was measured as a response to a threatening event.…”
Section: Discussionmentioning
confidence: 89%
“…In other species, the sex effect is not always obvious. For example, sex did not affect aggression in pigs (D'Eath and Lawrence, 2004), while sex ratio on the other hand (Crews et al, 2009;Mendl and Paul, 1990;Namikas and Wehmer, 1978) clearly affects aggression at least in rodents. However, aggression in the later studies was tested using conspecifics in a standard resident intruder test and in this study, aggression was measured as a response to a threatening event.…”
Section: Discussionmentioning
confidence: 89%
“…Previous research on the neural and behavioral consequences of CRS has identified 15 brain regions that play a role in stress reactivity as well as learning and memory (Tables S1 and S2 ). Assessing metabolic activity by using cytochrome histochemistry (23) in these nuclei, we find that nine nuclei capture 87% of the variance: basolateral amygdala (BLA), medial amygdala (MeAmy), central amygdala (CeAmy), anterior cortical amygdala (CoAmy), posteromedial cortical amygdala (PMCo), medial posterior dorsal amygdala (MePD), stria terminalis (ST), and CA1 and CA3 areas of the hippocampus (Table S2). V-L males subjected to CRS show an approximately 10% decrease in overall activity in the brain, but other experimental groups are relatively unchanged (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have deconstructed these two confounds and demonstrated that they have separate and distinct effects on the nature and quality of the individual's behavior later in adulthood, as well as on the metabolic activity in brain nuclei related to these behaviors. 73,76,77 The finding that functional neural systems can be re-organized, depending upon the composition of the litter in which the individual develops, is startling. Yet it yields a deeper understanding of how neural systems are organized early in life.…”
Section: Neural Mechanisms Underlying Sociosexual and Emotional Behavmentioning
confidence: 99%
“…Using this approach litters were reconstituted to control for sex ratio and genotype ratio. 76,77 Results indicate that sex and genotype of siblings in the litter affected aggressive behaviors as well as patterns of metabolic activity in limbic nuclei in the social behavior network later in adulthood. Moreover, this pattern in males varied depending upon the genotype of their brothers and sisters.…”
Section: Neural Mechanisms Underlying Sociosexual and Emotional Behavmentioning
confidence: 99%